A novel forward osmosis system in landfill leachate treatment for removing polycyclic aromatic hydrocarbons and for direct fertigation. (February 2017) - Li, Jing; Niu, Aping; Lu, Chun-Jiao; Zhang, Jing-Hui; Junaid, Muhammad; Strauss, Phyllis R.; Xiao, Ping; Wang, Xiao; Ren, Yi-Wei; Pei, De-Sheng
Abstract: Landfill leachate (LL) is harmful to aquatic environment because it contains high concentrations of dissolved organic matter, inorganic components, heavy metals, and other xenobiotics. Thus, the remediation of LL is crucial for environmental conservation. Here, a potential application of the forward osmosis (FO) filtration process with ammonium bicarbonate (NH4 HCO3 ) as a draw solution (DS) was investigated to remediate membrane bioreactor-treated LL (M-LL). After the leachate treatment, the toxicity and removal efficiencies of polycyclic aromatic hydrocarbons (PAHs) were evaluated using zebrafish and cultured human cells. The water recovery rate was improved using the current protocol up to 86.6% and 91.6% by both the pressure retarded osmosis (PRO) mode and the forward osmosis (FO) mode. Water flux increased with the increasing DS concentrations, but solution velocities decreased with the operation time. Toxicity tests revealed that the M-LL treated by NH4 HCO3 had no toxic effect on zebrafish and human cells. Moreover, green fluorescent protein (GFP) expression in the transgenic zebrafish Tg(cyp1a:gfp) induced by PAHs was very weak compared to the effects induced by untreated M-LL. Since the diluted DS met local safety requirements of liquid fertilizer, it could be directly applied as the liquid fertilizer for fertigation. In conclusion, this novel FO system using NH4 HCO3 as the DS provides a cheap and efficient protocol to effectively remove PAHs and other pollutants in LL, and the diluted DS can be directly applied to crops as a liquid fertilizer, indicating that this technique is effective and eco-friendly for the treatment of different types of LL. Highlights: A novel FO system using NH4 HCO3 as the DS was investigated. The FO system can effectively eliminate PAHs pollutants in landfill leachate. The diluted DS can be directly used as a liquid fertilizer. Landfill leachate treated by FO had no toxicity effects on zebrafish and human cells.